Identification of clinical factors associated with severe dengue among Thai adults: a prospective study - Vipa Thanachartwet (2017)
Background: Dengue is the most common mosquito-borne viral disease in humans. Recently, there has been an epidemic shift of dengue from mainly affecting children to affecting more adults with increased severity. However, clinical factors associated with severe dengue in adults have varied widely between studies. We aimed to identify the clinical factors associated with the development of severe dengue according to the World Health Organization (WHO)’s 2009 definition. Methods: We conducted a prospective study of adults with dengue admitted to the Hospital for Tropical Diseases in Bangkok, Thailand, from October 2012 to December 2014. Univariate and stepwise multivariate logistic regression analyses were performed. Results: Of the 153 hospitalized patients with confirmed dengue viral infections, 132 (86.3 %) patients had non-severe dengue including dengue without warning signs (7 patients, 5.3 %) and dengue with warning signs (125, 94.7 %). The rest (21, 13.7 %) had severe dengue including severe plasma leakage (16, 76.2 %), severe organ involvement (16, 76.2 %), and severe clinical bleeding (8, 38.1 %). Using stepwise multivariate logistic regression, clinical factors identified as independently associated with the development of severe dengue were: (1) being >40 years old (odds ratio [OR]: 5.215, 95 % confidence interval [CI]: 1.538–17.689), (2) having persistent vomiting (OR: 4.817, CI: 1.375–16.873), (3) having >300 cells per μL of absolute atypical lymphocytes (OR: 3.163, CI: 1.017–9.834), and (4) having lactate levels ≥2.0 mmol/L (OR: 7.340, CI: 2.334–23.087). In addition, increases in lactate and absolute atypical lymphocyte levels corresponded with severe dengue (p < 0.05). Conclusions: Our study identified several clinical factors independently associated with the development of severe dengue among hospitalized adults with dengue. This can aid in the early recognition and prompt management of at-risk patients to reduce morbidity and mortality.